Acquired Perforating Osteoma Cutis: A Rare Histopathological Diagnosis. (2nd January 2023) - Zipperer, Kate; Munoz, Ayezel; Kelly, Erica; Goodwin, Brandon
Abstract: Perforating osteoma cutis is a benign proliferation of mature bone within the dermis and subcutaneous tissue of the skin with transepidermal elimination. Transepidermal elimination of bone is the hallmark of perforating osteoma cutis and is defined by the breaching of bone through the epidermis. Perforating osteoma cutis is exceptionally rare because only 6 cases have been recorded in the literature at the time of preparation of this report. In this report, we present the case of a 65-year-old female patient with a medical history of nonmelanoma skin cancer, hypertension, hyperlipidemia, and type II diabetes mellitus presented for evaluation of a skin lesion of the posterior lower left leg, which had been present for 1 year. Clinical and histopathologic findings were consistent with the diagnosis of acquired perforating osteoma cutis. Treatment with surgical removal by tangential biopsy has thus far proven to be both diagnostic and therapeutic because no recurrence has been noted as of 6 months.